(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
As a continuation of two accompanying papers of ours, in this paper calculation is done relating to operational stresses in blades of horizontal mobile bandsaws as a part of their oper-ational characteristics. In the case of tensioning the blade by a spring mechanism, when the problem of the tensile forces and stresses is statically indeterminate, our solution (from the first accompanying paper) applies. This requires iterations which are programmed in an excel-file. In it, a number of formulas for stress calculation are programmed which are derived in our second accompanying paper. Several types of stress-components, and stress conditions, are in-volved. A series of additional computational results are obtained automatically with varying the input data in the excel-file. Stress oscillograms have been drawn, as well. They show that, under equal other conditions, the horizontal bandsaw blade is more threatened by fatigue than a vertical bandsaw blade.